Nonlinear scattering of non-breaking waves by a submerged horizontal plate : experiments and simulations - Tan, Keat Soon (2013)
Brossard et al. ([2009. Coastal Engineering 56, 11–22], hereinafter referred to as BPBD) presented an experimental study of the higher harmonics induced by a submerged horizontal plate and a submerged rectangular step. In this paper we present a numerical study of the wave scattering by a submerged thin plate as described in BPBD. A fully nonlinear numerical wave tank based on a desingularized boundary integral equation method (DBIEM) was developed for the interactions between non-breaking waves and a fixed 2D body. We also present a new set of experimental data on regular waves interacting with a submerged thin plate with different submergences, with the aim of removing the influences of multiple reflections between the wave-maker and submerged structures in a wave flume. We compare our numerical simulations with our experiments as well as the experiments of BPBD. The comparison shows that DBIEM can predict satisfactorily the multiple wave reflections caused by the thin plate as well as the main features of the generation and transmission of higher harmonic waves.